In vitro clonal propagation of ginger (Zingiber officinale Roscoe) var. Bentong through direct shoot and microrhizome organogenesis - Ahmad, Zahid Nisar (2021)
Bentong ginger is an important variety of Zingiber officinale Roscoe in Malaysia. Due to the poor flowering and seed set, ginger is vegetatively propagated through its rhizome. Using rhizome as planting material is bulky and has often caused yield loss due to the soil-borne disease's transmittance in ginger cultivation. Hence, micropropagation could be the best solution for these problems associated with ginger's conventional propagation. Therefore, the present study aims to optimize different stages of two different techniques (direct shoot regeneration and microrhizome induction) of Bentong ginger micropropagation. Bentong ginger rhizome sprouted bud explants were surface sterilized with 70% (v/v) ethanol for 1 minute and then followed by surface sterilizing with Clorox® (5.25% NaOCl) at 30, 40, 50, 60 and 70% (v/v) for 30 minutes. Using 70% Clorox® resulted in the highest percentage of aseptic cultures (75%), with 83.60% survivability in the culture medium. In the first experiment of shoot multiplication, the addition of different types of cytokinins (zeatin, 6-benzylaminopurine (BAP) and kinetin at 10 µM and thidiazuron (TDZ) at 5 µM) in Murashige and Skoog (MS) medium were assessed. Zeatin was found more effective than BAP, kinetin and TDZ for shoot multiplication of Bentong ginger. In the second experiment of shoot multiplication, zeatin at 0, 5, 10, 15 and 20 µM in combination with three different types of basal media vis MS, Linsmaier and Skoog (LS) and Gamborg et al. (B5) media was studied. MS medium supplemented with 10 µM of zeatin resulted in the highest number of shoots per explant (4.28) after six weeks of culture. In the last experiment of shoot multiplication, the addition of different types of auxins (indole-3-acetic acid (IAA), indole-3-butyric acid (IBA) and 1-naphthaleneacetic acid (NAA) at 0, 2.5, 5 and 7.5 µM) in MS medium supplemented with 10 µM zeatin was evaluated. The addition of 2.5 µM NAA in MS medium supplemented with 10 µM zeatin resulted in the highest number of shoots per explant (6.7) after eight weeks of inoculation. After shoot multiplication, the micropropagated plantlets were subjected to different growing media mixed of (1) soil + peat moss + vermiculite (1:1:1(v/v/v)), (2) soil + peat moss + perlite (1:1:1(v/v/v)), (3) soil + coco peat + vermiculite (1:1:1(v/v/v)), (4) soil + coco peat + perlite (1:1:1(v/v/v)) and (5) soil+ sand (1:1(v/v)). A growing media mixed of soil + coco peat + vermiculite resulted in the highest survival (94.8%) of the plantlets in the ex vitro conditions. The acclimatized plantlets were successfully established with a 100% survival in a shade house under a 50% black shade net. In the second part of the study, Bentong ginger's microrhizome induction was studied. In the first experiment, zeatin and BAP at 0, 5, 10, 15 and 20 µM in MS medium supplemented with 80 g L−1 sucrose and 2.5 µM NAA were examined for microrhizome induction of Bentong ginger. Zeatin was found more effective than BAP for microrhizome induction and 10 µM zeatin resulted in the highest number (4.50) and fresh weight of microrhizomes per explant (3.61 g) and the maximum diameter of microrhizome (7.82 mm). In the second experiment, different concentrations of sucrose (30, 45, 60, 75 and 90 g L−1 ) combined with NAA at 0, 2.5, 5 and 7.5 µM in MS medium supplemented with 10 µM zeatin were assessed. The addition of 60 g L−1 sucrose and 7.5 µM NAA in MS medium supplemented with 10 µM zeatin was the best combination for microrhizome induction. Finally, 93% of the microrhizomes were sprouted in the moist sand inside a room and 100% of the sprouted microrhizomes were successfully established in the open field conditions. In conclusion, both micropropagated plantlets and microrhizomes can be used as disease-free planting materials for the commercial cultivation of Bentong ginger.